Comparative assessment of two proxies of fish discard survival. (March 2019) - Morfin, Marie; Kopp, Dorothée; Benoît, Hugues P.; Méhault, Sonia
Highlights: The two most used vitality indices of fish discard survival are very correlated. Some redundancies and inconsistencies were detected within one of the indices. Both indices responded similarly to stressing factors. One of the indices is deemed superior given the ease of data collection. Abstract: Two vitality index approaches have been demonstrated to be good proxies of discard survival in similar fishing and environmental conditions: Reflex Action Mortality Predictors combined with injuries (RI) scores that measure the proportion of impaired reflexes and injuries, and a simpler, quicker, but less precise approach based on ordinal categories related to fish body movements and injuries (semi-quantitative assessment, SQA). This study assessed and compared these two approaches for five species (two flatfishes, skates, a seabass and a catshark) discarded in a coastal otter trawl fishery in the Bay of Biscay. All species displayed good vitality status according to both indices and were not very sensitive to the fishing nor their biological conditions. Still, flatfishes were more sensitive to discarding while the catshark was very resistant. Furthermore, depending on species, the impairment of some reflexes and injuries were associated to stressing factors, highlighting the potential of the approach but also the complexity involved in building a relevant score. The SQA index was highly correlated with the RI score and was sensitive to more sources of stressing factors for similar predictive performance. While the relevance of these two approaches should be ultimately determined by the strength and consistency of their association with discard survival, these results suggest that the RI approach was not more effective than SQA despite the extra labour and time involved in collecting the data.